Implementasi Prinsip Syariah untuk Meningkatkan Kualitas Laporan Keuangan dan Kepercayaan Investor - Elly Yanti; Dwi Aryaningsi; Ardina Rasti; Masyhuri Masyhuri (INDO PUBLISHING, 2026)
This study aims to examine the implementation of Sharia principles in the preparation of financial statements and their impact on information quality and investor trust. The method used is a qualitative approach through a literature review. Principles such as honesty, transparency, accountability, and fairness form the basis for presenting reliable financial information. The results show that the application of Sharia principles enhances the credibility of financial statements, reduces manipulative practices, and minimizes information asymmetry between management and investors. This leads to increased investor trust and a stronger corporate image. This study is expected to serve as a reference for developing financial reporting practices that emphasize integrity and public trust.